Research Trends Of Computational Thinking For Advancing Sustainable Development Goals (SDGs) In Science Learning: Bibliometric Analysis - Alfian Erwinsyah; Yusuf, Frida Maryati; Laliyo, Lukman A.R; Mursalin; Inga Riumkina (Universitas Negeri Semarang, 2025)
Computational Thinking (CT) emerged as a crucial competency that bridges digital literacy and scientific problem solving in the context of achieving Sustainable Development Goal (SDG) 4 on quality education. However, the model of integrating CT in science learning is still poorly explored, hindering progress towards SDG Targets 4.4 (technical skills) and 4.7 (scientific literacy). This study is the first bibliometric analysis to map the trends of CT research in science learning (2021–2023) through Scopus. The novelty lies in the identification of global collaboration patterns, knowledge gaps, and research priorities that are aligned with the 2030 Agenda. Three research questions were guided: (1) Publication distribution, (2) Dominant journals and subject areas, (3) Keyword dynamics/co-occurrence networks. Data retrieved from Scopus using the strings TITLE-ABS-KEY(